Profiling Laboratory Biomarkers Associated with COVID-19 Disease Progression: A Single-Center Experience - Maria Khan; Noman Shah; Hina Mushtaq; Valeed Jehanzeb (International Journal of Microbiology)
Background. There is clinical importance to investigate the disease progression through potential biomarkers of SARS-CoV-2 infection. In the present study, we aim to evaluate the significance of inflammatory markers in different categories of COVID-19 in admitted patients. Methods. In a single-center, observational study of 50 in-hospital patients who were diagnosed with COVID-19 and admitted to the intensive care unit of a tertiary care hospital in Peshawar, infection biomarkers, including hs-CRP, serum ferritin, serum creatinine, ALT, ALP, cardiac troponin-I, and IL-6 were analyzed. Results. The median age was 61.3 years. 70% (35) were male while 30% (15) were female. We noted significantly increased hs-CRP (9.32 mg/dL ± 10.03) and ferritin levels (982.3 ng/ml ± 601.9). A noteworthy increase was observed in neutrophil count (11.05 × 109/L) and a decrease was observed in lymphocyte count (0.27 × 109/L) (P<0.05), and the platelet count was borderline decreased (244.1 × 109/L). IL-6 levels were markedly increased in all admitted patients (100.2 pg/ml ± 122.2 pg/ml). Conclusion. The serum levels of CRP, troponin-I, ALP, ALT, serum creatinine, and ferritin are markedly increased in COVID-19 patients. Increased CRP and ferritin levels were also associated with secondary bacterial infection and poor clinical outcomes.